Risk Factors and Clinical Characteristics of Neonatal Acute Respiratory Distress Syndrome Caused by Early Onset Sepsis - You, Ting; Zhou, Yan-Rong; Liu, Xiao-Chen; Li, Lu-Quan (Frontiers in Pediatrics, 2022)
Purpose To identify the risk factors associated with the development of acute respiratory distress syndrome (ARDS) in early onset sepsis (EOS) infants and their clinical features. Methods A retrospective study was conducted at Children’s Hospital of Chongqing Medical University between Jan 2000 and Oct 2020. Infants were divided into ARDS and Non-ARDS groups. Clinical characteristics and risk factors were compared between two groups. Results Two hundred and fifty infants (58 with ARDS) were included. Smaller gestational age (GA), lower birth weight (LBW), lower serum albumin level, higher rate of preterm, premature rupture of membranes, antenatal steroid exposure and lower Apgar score were associated with the increasing development of ARDS by univariate analysis (P<0.05). LBW (β=-0.001, P=0.000, OR:0.999, 95CI:0.998-0.999) and low serum albumin level (β=-0.063, P=0.022, OR:0.939, 95CI:0.889-0.991) were identified as independent risk factors for the development of ARDS by logistic regression analysis. Higher frequency of complications and mortality was observed in ARDS group. EOS caused by gram positive bacteria with Extended-Spectrum Beta-Lactamases (ESBL)-positive had higher rate of the development of ARDS. The bacteria of EOS showed a high sensitivity to Amikacin + teicoplanin or vancomycin. Conclusions ARDS in EOS may lead to higher frequency of complications and mortality. The risk factors for the development of ARDS were LBW and low serum albumin level.